If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2xy + -5 + x + 3xy + 10 = 0 Reorder the terms: -5 + 10 + 3x + x + 2xy + 3xy = 0 Combine like terms: -5 + 10 = 5 5 + 3x + x + 2xy + 3xy = 0 Combine like terms: 3x + x = 4x 5 + 4x + 2xy + 3xy = 0 Combine like terms: 2xy + 3xy = 5xy 5 + 4x + 5xy = 0 Solving 5 + 4x + 5xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 4x + -5 + 5xy = 0 + -5 Reorder the terms: 5 + -5 + 4x + 5xy = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4x + 5xy = 0 + -5 4x + 5xy = 0 + -5 Combine like terms: 0 + -5 = -5 4x + 5xy = -5 Reorder the terms: 5 + 4x + 5xy = -5 + 5 Combine like terms: -5 + 5 = 0 5 + 4x + 5xy = 0 The solution to this equation could not be determined.
| 6/x=3/7 | | 480-8y=8 | | -2=w/-5 | | 6+w=12 | | 2(5x-31*x)= | | 9e-2=5e+26 | | 22x+26=48 | | y=0(8)+8 | | 120=(x+1)(x+20) | | 10/5x^2-20x-60=0 | | 3/4*6=c | | 2(5x-31)(2x)= | | -7(x+1)=43 | | -27+s=42 | | p+1/4/3=4/5/8 | | 26-2x=16 | | 6x^2+(-10x)+6+4x+(-5)= | | 22-2=4 | | -5x+6(3x-6)=-15-8x | | 7(2x+5)-7=32 | | 2x+(-6x)+(-5x)= | | 7/11x+(-17)=4 | | J/7=10-9j | | 11x+7=51 | | 12=(3m-17) | | (-6x)+(-x)= | | (-3x)+(-4x)+3x= | | 3=278y | | 1/3+2/3 | | -3/4m=-9/16 | | P+11/3=45/8 | | 3x/5-x/3=4 |